Preparation of the capillary copper/titanium composite pipe by floating-plug drawing processing and its microstructure and properties - LIU Xin-hua; LIN Yi-liang; FU Hua-dong; LIU Xue-feng; XIE Jian-xin (工程科学学报, 2017)
A copper/titanium bimetallic composite pipe with high interfacial bonding quality was manufactured by the high-temperature rotary swaging forming, and then was processed by the floating-plug drawing process. The forming ability of drawing process and the effect of drawing process on the microstructure and properties of the product were mainly investigated. The results show that the floating plug drawing, especially the wall-reduction drawing, has a great destructive effect on the bonding interface of the pipe, which results in that it is difficult to carry out multi-pass continuous drawing, and single pass drawing volume should not reach over 30%. The annealing at 575℃ for 70 min has little effect on the diffusion of interfacial elements, but it can reduce the work hardening and residual stress. This process makes the pipe's average peel strength increase from 7. 8 N·mm-1 (worked state) to 17. 1 N·mm-1 (annealed state), which considerably improves the subsequent drawing performance of the pipe. A reasonable drawing forming process for the copper/titanium composite pipe was made based on the strict control of drawing wall-reduction, and a capillary size pipe with an excellent bonding property was successfully prepared.